(3JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdYeGdGJ GdTQYjIs - (3CHh GdMSf Ydj Hf eMeO Hf CMeO Hf ehSi Hf eSYhO Hf CHi ZaQI GdNRGYi GHf Pi GdhRGQJjfs; (3GHf XgjQI , eMeO Hf eMeO Hf CHj HcQ Hf Ydj Gdecj GdeNRhej, LeGd GdOjf,J (B986 (3g` s ((3eMeO dHjH s)
(3ChdgG (B:s
(3jJab ChdgG eY Chd GdfSNI GdChdi s
(3BNQgG (B:s
(3aCeG eG QhGg CHh GdYHGS adjS dg eYfi jUM , fbdJg Yf WQI cJHgG Ydi GdHjJjf ai fSNJg ef GdcGed GdJi cJHgG HNWg hbQCgG Ydi GHf GdSjO GdHWdjhSi GfJgi GdLRA GdChd hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3HBNQgG agQS dCHhGH GdLRA haUhdgs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs